FILSAFAT ILMU DALAM ISLAM: SEBAGAI BASIS INTEGRASI - Humaidi Humaidi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2022)
The main issues of the philosophy of science are, first, to examine science itself and its aspects like the meaning and nature of science, its form and kinds, objects, sources and method of obtaining, the relationship between subject and object, and the benefits and objective of science. The second issues is the study of the methodological aspects. This field has a significant role in determining and measuring the validity and truth of human knowledge. In addition, the philosophy of science functions as a liaison, integrate, and harmonize between one science and another. Therefore, it can be said that there is no integration and harmony between various branches of knowledge without a philosophy of science. This conclusion can be true and valid if it is based on the principle of the philosophy of science in Islam. The conclusion will be different if the teaching of philosophy of science is based in the perspective of secular philosophy. The purpose of this study is to analyze the role, position, and function of philosophy in studying science in terms of sources, object, benefits, methods of obtaining, and the relation between one knowledge and another. This type of research is qualitative based on library sources using a deductive rational analysis and approach.